The Nobel Prize winning discoveries in infectious diseases - Rifkind, David (Elsevier/Academic, 2005)
This book presents the 24 discoveries in infectious diseases that have merited Nobel Prize recognition since the inception of the awards in 1901. Grouped according to biological groups rather than chronology, each discovery includes a biographical sketch of the laureate(s), a description of the research, and a summary of the current status of the field. In addition, consideration is given to the relevance of the research on the general field of biology and medicine.